Goode on commercial law - Goode, Royston Miles; McKendrick, Ewan (London ; Dayton, Ohio : LexisNexis, 2009)
Offers coverage of commercial law in both a national and an international context. This book combines a theoretical analysis with a practical approach which examines the theory in the context of typical commercial and financial agreements, both domestic and international
1. The foundations of commercial law -- 2. Domestic sales -- 3. Money, payment and payment systems -- 4. Secured financing -- 5. Specific forms of secured business finance -- 6. Corporate insolvency -- 7. International trade and finance -- 8. The resolution of commercial disputes -- 9. Envoi
Previous ed.: London : LexisNexis, 2004
Includes bibliographical references and index
Keywords: Commercial law -- England; Commercial law -- Wales